Odpowiedzi

2010-04-15T16:46:28+02:00
A )
2+3m=5-5m
3m+5m=5-3
8m=2
m=¼

b )
4(x+3) = 5x-19
4x+12=5x-19
4x-5x=-19-12
-x=-31
x=31

c )
2(2m-3) + 2m = 5 (3-m) +1
4m-6+2m=15-5m+1
4m+2m+5m=15+1+6
11m=22
m=2

d)
1,2 - 1,9x= 0,5(x+3) -0,3(x+5)
1,2-1,9x=0,5x+1,5-0,3x-1,5
-1,9x-0,5x+0,3x=1,5-1,5-1,2
-2,1x=-1,2
x=⁴/₇
2010-04-15T16:48:26+02:00
A)
2+3m=5-5m
3m+5m=5-2
8m=3/8
m=3/8
b)
4(x+3) = 5x-19
4x+12=5x-19
4x-5x=-19-12
-x=-21//(-1)
x=21
c)
2(2m-3) + 2m = 5 (3-m) +1
4m-6+2m=15-5m+1
4m+2m+5m=15+1+6
11m=22//11
m=2
d)
1,2 - 1,9x= 0,5(x+3) -0,3(x+5)
1,2-1,9x=0,5x+1,5-0,3x-1,5
-1,9x-0,5x+0,3x=-1,2
-2,1x=-1,2/-(2,1)
x=0,6